Analisis Kesulitan Konseptual Mahasiswa Dalam Memahami Mata Kuliah Kalkulus Trigonometri Lanjutan - Irvan Malay; Muhammad Guntur Surbakti; Abdul Rofig Sagala; Ria Trisa Yosefa Sarumpaet; Zikry Habib Ramadhan (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze and identify the types of conceptual difficulties experienced by students in understanding the material in the Calculus course, especially Advanced Trigonometry. Difficulties in this course are often the main obstacle for students to master other advanced mathematical concepts. This study used a qualitative approach with descriptive methods, involving first-semester electrical engineering students. Data were collected through diagnostic tests covering the material of derivatives, integrals, and infinite series of trigonometric functions, as well as semi-structured interviews to explore the reasons behind incorrect answers. The results showed that the main conceptual difficulties of students were divided into three categories: (1) Difficulty in associating basic trigonometric identities with calculus operations, (2) Difficulty in understanding problems and their application in calculating area or volume (integrals), and (3) Difficulty in presenting or explaining the theory of trigonometric functions and their derivatives. These findings underscore the need for the development of learning strategies that focus more on a deeper understanding of basic trigonometric concepts before integrating them with advanced calculus concepts, as well as the use of more effective visualization methods in lectures.